2020
DOI: 10.1186/s13287-020-1574-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SW033291 on the myogenesis of muscle-derived stem cells and muscle regeneration

Abstract: Background: The unmet medical needs in repairing large muscle defects promote the development of tissue regeneration strategy. The use of bioactive molecules in combination with biomaterial scaffold has become an area of great interest. SW033291, a small-molecule inhibitor targeting 15-hydroxyprostaglandin dehydrogenase (15-PDGH) and subsequently elevating the production of prostaglandin E2 (PGE2), has been proved to accelerate the recovery and potentiate the regeneration of multiple tissues including the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In vitro , SW033291 enhanced myogenic differentiation and myotube formation via upregulating a series of myogenic markers with an activated PI3K/Akt pathway involved. Additionally, SW033291 incorporating the compound with MDSCs in fibrin gel significantly facilitates myofiber formation within the defect region with mild immune response, less fibrosis, and sufficient vascularization 143 . Together with these findings, PGE2 can facilitate the proliferation and differentiation of MDSCs.…”
Section: The Role Of Pge2 On Organ Repair and Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro , SW033291 enhanced myogenic differentiation and myotube formation via upregulating a series of myogenic markers with an activated PI3K/Akt pathway involved. Additionally, SW033291 incorporating the compound with MDSCs in fibrin gel significantly facilitates myofiber formation within the defect region with mild immune response, less fibrosis, and sufficient vascularization 143 . Together with these findings, PGE2 can facilitate the proliferation and differentiation of MDSCs.…”
Section: The Role Of Pge2 On Organ Repair and Regenerationmentioning
confidence: 99%
“…Researchers have successively clarified the repair capabilities of SW033291 in different injury models including liver resection 80 , I/R renal injury 22 , intestinal injury 80 , bone marrow transplantation 80 , 155 , 156 , bone marrow failure 166 , muscle defect 143 , or muscle aging 3 , which we have mentioned above. In fact, SW033291 was also explored in aspects of cervical ripening, drug-induced kidney injury, and pulmonary fibrosis.…”
Section: Pge2-based Therapeutic Strategies For Tissue Regenerationmentioning
confidence: 99%
“…17 Subsequent studies demonstrated that SW033291 promotes splenic niche hematopoietic regeneration, bone regeneration, and skeletal muscle regeneration. [26][27][28][29] Other observed beneficial effects of SW033291 include suppression of pulmonary fibrosis and protection from renal injury. 18,19,[30][31][32] Our findings establish a previously unrecognized cardioprotective action of SW033291, and further highlight the potential of 15-PGDH inhibitors to block fibrosis across organ systems.…”
Section: -Pgdh Inhibition As a Potential Therapy For Cardiac Diseasementioning
confidence: 99%
“…In the field of TE to treat volumetric muscle loss defects, MDSCs, which adhere to scaffolds, can also play an important role, which has presented promising prospects for translating this method into the treatment of severe sarcopenia [ 77 , 78 ]. Dong et al [ 79 ] concluded that SW033291, a small-molecule inhibitor targeting 15-hydroxyprostaglandin dehydrogenase that subsequently elevates the production of prostaglandin E2 (PGE2), could promote the myogenic differentiation of MDSCs, which led to the repair of large skeletal muscle defects. Tamaki et al [ 80 , 81 ] successfully formed cardiomyocytes after myocardial infarction with the help of CD34( +)/CD45(−) MDSCs and suggested the possible future use of these cells for cardiac muscle repair in infarcted areas.…”
Section: Mdscs and Sarcopeniamentioning
confidence: 99%